2017
DOI: 10.1038/s41598-017-06251-7
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Phase Contrast Tomography Reveals Early Vascular Alterations and Neuronal Loss in a Multiple Sclerosis Model

Abstract: The degenerative effects of multiple sclerosis at the level of the vascular and neuronal networks in the central nervous system are currently the object of intensive investigation. Preclinical studies have demonstrated the efficacy of mesenchymal stem cell (MSC) therapy in experimental autoimmune encephalomyelitis (EAE), the animal model for multiple sclerosis, but the neuropathology of specific lesions in EAE and the effects of MSC treatment are under debate. Because conventional imaging techniques entail pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…In contrast, recent works demonstrated that X-ray phasecontrast tomography (XPCT) enables the visualization of the 3D distribution of neuronal and vascular network of the whole spinal cord (Fratini et al, 2015;Cedola et al, 2017), with a micrometric to sub-micrometric spatial resolution with a simple and rapid sample preparation. In conventional radiography, the collected transmitted intensity is formed by the interaction of the incident X-ray beam with absorbing structures inside the sample.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, recent works demonstrated that X-ray phasecontrast tomography (XPCT) enables the visualization of the 3D distribution of neuronal and vascular network of the whole spinal cord (Fratini et al, 2015;Cedola et al, 2017), with a micrometric to sub-micrometric spatial resolution with a simple and rapid sample preparation. In conventional radiography, the collected transmitted intensity is formed by the interaction of the incident X-ray beam with absorbing structures inside the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of X-ray Phase Contrast imaging (XPCi) are rapidly expanding, thanks to its ability to visualize and quantify features invisible to conventional X-ray imaging techniques on scales spanning from tens of microns to nanometers. [1][2][3][4][5] While for a long period this technique was limited to synchrotron radiation facilities, the development of new phase detection methodologies now enables XPCi with laboratory-based sources. [6][7][8][9][10] Despite XPCi not yet being available in hospitals, the improved visualization capabilities demonstrated so far suggest that healthcare would strongly benefit from a widespread application of XPCi.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that X-ray phase contrast micro-tomography (XrPCµT) enables the study of the vascular and neuronal networks simultaneously without sample sectioning [25]. In particular, XrPCµT imaging is a multiscale (spanning from mm to <µm) 3D imaging technique that can be used to evaluate morphological alterations in central nervous system (CNS) tissue [26]. However, XrPCµT images are characterized by small intensity variations which make the segmentation process challenging.…”
Section: Introductionmentioning
confidence: 99%